Meningkatkan Pemahaman Konsep pada Materi Siklus Air dengan Menggunakan Model Probem Based Learning (PBL) Berbasis Media Diorama Siklus Air di Sekolah Dasar Negeri 066055 Medan - Situmorang, Rumiris; Ammy, Putri Maisyarah; Simatupang, Mesli (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study investigates the effectiveness of Water Cycle Diorama media integrated with the Problem-Based Learning (PBL) model in enhancing fourth-grade elementary students’ conceptual understanding of the water cycle. The research was motivated by the students' difficulty in visualizing and comprehending the dynamic processes within the water cycle. Utilizing classroom action research across two cycles—comprising planning, action, observation, and reflection—this study was conducted at SD Negeri 066055 Medan. Data collection involved conceptual understanding tests and observation of student participation. The findings revealed a notable improvement in learning outcomes, with the percentage of concept mastery rising to 67% in the first cycle and reaching 100% in the second cycle. The implementation of the Water Cycle Diorama media significantly fostered active engagement and increased enthusiasm among students. Furthermore, the PBL approach supported deeper and more concrete comprehension of abstract scientific processes. These results emphasize the importance of integrating innovative, learner-centered strategies into science instruction at the primary level to promote meaningful learning and long-term conceptual retention.